2018
DOI: 10.1039/c8py00193f
|View full text |Cite
|
Sign up to set email alerts
|

Linear dendronized polyols as a multifunctional platform for a versatile and efficient fluorophore design

Abstract: Linear dendronized polyols (LDPs)as a modular platform for bright, stable, and biocompatible polymeric fluorophores applicable for fluorescent bioimaging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The DASP scaffold allows flexible incorporation of additional fluorophores (Figure d). Benefiting from the livingness of ROMP-based synthesis, fluorophores could be easily incorporated into the DASP scaffold in the polymerization stage, as long as the corresponding fluorophore-bearing monomer was available. ,, For example, fluorescein moieties could be copolymerized into the arms using a fluorescein-functionalized norbornenyl monomer ( FL-NB , see the Supporting Information for details), and because of the innate fAIE fluorescence from DASP 5 ’s core, a FRET-based imaging agent would then form, generating a DASP scaffold ( FL-DASP ) with green fluorescence (Figure S5a). The ratio of 1:FL-NB : 3 could be easily tuned (Table S2 and Figure S11), which affected the energy transfer efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DASP scaffold allows flexible incorporation of additional fluorophores (Figure d). Benefiting from the livingness of ROMP-based synthesis, fluorophores could be easily incorporated into the DASP scaffold in the polymerization stage, as long as the corresponding fluorophore-bearing monomer was available. ,, For example, fluorescein moieties could be copolymerized into the arms using a fluorescein-functionalized norbornenyl monomer ( FL-NB , see the Supporting Information for details), and because of the innate fAIE fluorescence from DASP 5 ’s core, a FRET-based imaging agent would then form, generating a DASP scaffold ( FL-DASP ) with green fluorescence (Figure S5a). The ratio of 1:FL-NB : 3 could be easily tuned (Table S2 and Figure S11), which affected the energy transfer efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zimmerman et al reported PGD-based dendronized polyols and used them as scaffolds for the construction of fluorophores. However, as PGDs have very small repeating units, dendronized polymers based on low-generation ( g ) PGDs ( g ≤ 3) are in fact flexible and could be intramolecularly cross-linked. , These linear polyPGDs provided only limited site isolation for encapsulated hydrophobic moieties in an aqueous environment, presumably because of core collapse and the formation of pearl necklace structures , that lead to the exposure of inner cavities and quenching of encapsulated dyes. Thus, this strategy is not universal and may still require the synthesis of high-generation dendrons for better performance.…”
Section: Introductionmentioning
confidence: 99%
“…The striking photostability of PBI expressed in long fluorescence lifetimes of ≈4–5 ns and monoexponential fluorescence decays over at least 16 ns becomes obvious in comparison to other conventional fluorescent probes such as cy5 (0.91 ns), alexa fluor 647 (1.04 ns), and rhodamine B (1.74 ns) with significantly lower lifetimes. The superior long‐term photostability of PBIs compared to common fluorophores like coumarin or fluorescein was recently demonstrated in a study by Zimmerman and co‐workers; additionally, they were able to improve the FQYs of PBIs by site‐isolation of the fluorophore in the imide positions. However, a major drawback of PBI‐based dyes is their aggregation tendency in aqueous solution caused by the polyaromatic scaffold of the PBI cores resulting in fluorescence quenching.…”
Section: Introductionmentioning
confidence: 94%
“…The larger space occupancy by fluorine atoms enable the fluoroalkyl chains to attain an all- trans helical conformation in comparison to the zigzag geometry adopted by hydrocarbon chains. , Consequently, the fluorinated amphiphiles are more rigid and persist in an orderly packed structure, which allows the formation of stable aggregates with different supramolecular assemblies such as membranes, ribbons, films, vesicles, and even complex morphologies like perforated bilayer vesicles. ,, Furthermore, these well-organized assemblies possess less surface curvature and improved drug encapsulation ability. For this reason, a diverse variety of fluorinated amphiphiles have been synthesized and reported in the literature. , Recently, Huang et al, synthesized fluorinated polymeric architectures for cancer treatment. Haag et al.…”
Section: Introductionmentioning
confidence: 99%